Medication non-adherence and its associated factors among kidney transplant patients in a large teaching hospital in Ethiopia - Meskerem Nimani Derejie; Erimas Nimane Dereje; Dirijit Mamo Alemu; Yemane Gebremedhin Tesfay; Fufa Hunduma; Negash Miniwye Temie (BMC Nephrology)
Abstract Background This study examines medication adherence among kidney transplant patients at St. Paul’s Hospital Millennium Medical College (SPHMMC) in Addis Ababa, Ethiopia, focusing on the level of adherence and associated factors to immunosuppressant medicines. Methods and materials A cross-sectional study was conducted on 270 patients from October 2021 to January 2022 using a structured questionnaire analyzed with SPSS version 26. The prevalence of medication adherence was computed, and a binary logistic regression was fitted to estimate the association. Medication adherence level measurement in post-kidney transplant patients was assessed using the Simplified Medication Adherence Questionnaire (SMAQ) and Basel Adherence Assessment Scale in Immunosuppressants (BAASIS). A 95% confidence interval and p-value < 0.05 were used for statistical significance. Results The study found that 71.5% of kidney transplant patients were male, with a median age of 37 and a mean duration of 3.55 years. Medication adherence in post-kidney transplant patients was 81.9%. Post-transplant duration above 5 years and missing follow-up visits more than two times was associated with a 92.6% and 91.2% in medication non-adherence rate respectively. Additionally, forgetfulness was associated with a 90.6%, non-adherence level compared to drug unavailability and financial reasons. Conclusion and recommendation The study indicates that our patients exhibit higher medication adherence than WHO-measured levels, suggesting the need for healthcare providers to strengthen their intervention, especially for those above 5 years post-kidney transplant. The reason for increased adherence could be explained by the health education program about the medication name, dosing, frequency of ingestion and adverse effects of the drug, and effects of non-adherence.